Is There a Role for Hematopoietic Growth Factors During Sepsis? - Chousterman, Benjamin G.; Arnaud, Marine (Frontiers in Immunology, 2018)
Sepsis is a complex syndrome characterized by simultaneous activation of pro- and anti-inflammatory processes. After an inflammatory phase, patients present signs of immunosuppression and possibly persistent inflammation. Hematopoietic growth factors (HGFs) are glycoproteins that causes immune cells to mature and/or proliferate. HGFs also have a profound effect on cell functions and behavior. HGFs play crucial role in sepsis pathophysiology and were tested in several clinical trials without success to date. This review summarizes the role played by HGFs during sepsis and their potential therapeutic role in the management sepsis-related immune disturbances.